Using coherent X-rays to follow dynamics in amorphous ices. Issue 6 (13th September 2022) - Ladd-Parada, Marjorie; Li, Hailong; Karina, Aigerim; Kim, Kyung Hwan; Perakis, Fivos; Reiser, Mario; Dallari, Francesco; Striker, Nele; Sprung, Michael; Westermeier, Fabian; Grübel, Gerhard; Nilsson, Anders; et al.
Abstract : Amorphous ice plays an important role in our overall understanding of water's phase diagram. Abstract : Amorphous solid water plays an important role in our overall understanding of water's phase diagram. X-ray scattering is an important tool for characterising the different states of water, and modern storage ring and XFEL facilities have opened up new pathways to simultaneously study structure and dynamics. Here, X-ray photon correlation spectroscopy (XPCS) was used to study the dynamics of high-density amorphous (HDA) ice upon heating. We follow the structural transition from HDA to low-density amorphous (LDA) ice, by using wide-angle X-ray scattering (WAXS), for different heating rates. We used a new type of sample preparation, which allowed us to study μm-sized ice layers rather than powdered bulk samples. The study focuses on the non-equilibrium dynamics during fast heating, spontaneous transformation and crystallization. Performing the XPCS study at ultra-small angle (USAXS) geometry allows us to characterize the transition dynamics at length scales ranging from 60 nm–800 nm. For the HDA-LDA transition we observe a clear separation in three dynamical regimes, which show different dynamical crossovers at different length scales. The crystallization from LDA, instead, is observed to appear homogenously throughout the studied length scales.